Some Aspects of the Biology and Ecology of Neurothemis Tullia (Drury) (Odonata:Libellulidae) in the Laboratory and Rainfed Rice Field in Peninsular Malaysia - Md Rawi, Che Salmah (1996)
The life cycle, life history, feeding biology and ecology of Neurothemis tullia (Drury) larvae and adults were studied from June 1993 through April 1995 in a rice field of Bandar Baru District in Kedah, Malaysia. An aquatic net was used to sample the lar.-ae in the field and the adult ecology was studied using visual counting and Mark-Release-Recapture (MRR) techniques. The results showed that the egg incubation period was eight days followed by forty four days of larval developmental period in the laboratory. Thus, the mean life cycle from egg to adult emergence was fifty two days. Growth of both head capsule and body length was faster from instar one to six and slowed gradually at higher instars. Larval development was asynchronous and a maximum of eight different instars was found at one sampling occasion. Four emergences were observed in the year of 1994. The onset of emergence occurred in March, May, July and October, 1994. The size of emerging populations varied according to the availability of water during larval growth and rice growing phases. Some of the larvae were able to survive in the rice field during short dry periods of less than four weeks. The abundance of the larvae was higher in 1994 compared to 1993. Generally more larvae were found during tiller, mature field and fallow phases of rice cultivation. No correlation was found between the abundance of the larvae and any of the water parameters i.e. temperature, pH, dissolved oxygen, conductivity, nitrate, phosphate, chlorophyll a and height of plants. The availability of water in the field however, determined the presence or absence of the larvae. Fifty one aquatic animal taxa coexisted with N. tullia of which the abundance of each of Orthetrum sabina (Drury), Anisoptera, Anopheles spp., Chironomidae, Corixidae and hemipteran Veliidae correlated positively with that of N. tullia. A hypothetical trophic relationship of N. tullia in the rice field is proposed. The highest estimated population of adults was 2400 individuals per 4.6 ha (-522 adults per ha). The male population peaked slightly earlier than the female population, possibly an indication of longer maturation period of the females. Adult populations were high when rice plants were growing in the field but decreased drastically after harvest. Prolonged drought further reduced the adult population density . A general pattern of adult abundance was obtained either by MRR technique or visual count method with the former generating more information than the latter. Survival rates of both male and female adults of N. tullia were >0.5 throughout the study. The mean life span durations were 42.4 and 36.5 days and the maximum life span durations were sixty five and fifty three days, respectively. The populations of N. tullia were unstable because the proportions of age classes varied through time. The adults were widely distributed within its home range of about 40 m. Their maximum distance travelled was approximately 130 m. The adults started feeding as early as 0730 hrs with two peaks of heaviest gut weights at 1030 hrs and 1730 hrs. At anytime of the day, the females guts were significantly heavier than the guts of the males (ANOVA, P=0.05) reflecting higher feeding activity and nutritive requirement by the females.